Influence of wildfire severity on plant and bird species richness, diversity and composition - Liubov Volkova; Julian Di Stefano; Eliza K. Thompson; Christopher J. Weston (Discover Conservation)
Abstract Fire is a key driver of forest ecosystem structure and function, influencing the distributions of both plants and animals. Australia’s Black Summer wildfires of 2019–2020 burnt through over 9 M ha of land including about 7.6 M ha of temperate Eucalyptus forest over several months. This is an unprecedented scale of fire when considering the last few centuries of fire history in south-eastern Australia. This study assessed a 1983 regenerated Eucalyptus forest for plant and bird diversity in 2016, 4 years prior to the Black Summer wildfires, and again in November 2020, eleven months after the wildfires. With a range of fire severities resulting from previous fuel reduction treatments, the before and after wildfire biodiversity assessments allowed the investigation of fire severity impacts on plant and bird diversity. Species richness, Shannon’s diversity, and community composition were studied using mixed effects models and community composition was analysed using multivariate generalised linear models. The results showed that wildfire severity had no impact to plant species richness, diversity or composition. Although wildfire severity had no significant effect on plant species diversity, 33% of previously recorded plant species were not present almost a year after the wildfire, while 22% of previously unrecorded species appeared. Overall, 46 bird species were observed across all sites, with 38 species observed prior to and 28 species observed after wildfire. The bird species diversity was reduced, with a shift to a greater abundance of insectivorous birds after the wildfire. This study enhances our understanding of the impact of fire severity on plant and bird species diversity and provides valuable information for managers to refine fuel reduction practices to mitigate fire impact on biodiversity.